Relationship between the activity of the genioglossus, other peri-pharyngeal muscles and flow mechanics during wakefulness and sleep in patients with OSA and healthy subjects - Oliven, Ron (Respir Physiol Neurobiol, 2019)
INTRODUCTION: In patients with OSA, substantial increases in genioglossus (GG) activity during hypopneas/apneas usually fail to restore normal airflow. The present study was undertaken to evaluate if this phenomenon can be explained by reduced activation of other peri-pharyngeal muscles. METHODS: We recorded EMGs of the GG and four other peri-pharyngeal muscles (accessory dilators, AD), in 8 patients with OSA and 12 healthy subjects, during wakefulness and sleep. Repetitive events of flow limitation were induced during sleep. The events with the highest increases in AD activity were evaluated, to assess if combined activation of both the GG and AD to levels higher than while awake ameliorate airflow reduction during sleep. RESULTS: Flow limitation triggered large increases in GG-EMG, but only modest augmentation in AD activity. Nevertheless, phasic EMG activity was present in 40 % of the ADs during sleep. In multiple events, increases of both GG and AD activity to levels substantially higher than while awake were not associated with improvement in airflow. CONCLUSIONS: We conclude that sleep-induced reduction in AD response to airway obstruction cannot completely explain the failure of upper airway dilators to maintain pharyngeal patency. We speculate that reduction in dilator muscle efficacy may be due to the alterations in motor units recruitment patterns during sleep.